Saphenous reflux patterns in C2 patients: A record of 1196 ultrasound reports. (July 2020) - Coelho Neto, Felipe; de Oliveira, Rodrigo Gomes; Gregório, Emerson Pereira; Belczak, Sergio Quilici; de Araujo, Walter Junior Boim
Objectives: To describe saphenous reflux patterns in patients classified as CEAP C2 by analysis of 2027 vascular ultrasound examination reports. Methods: A total of 2027 venous mapping studies were reviewed and 1196 patients classified as CEAP C2 were selected. Patients were classified according to patterns of reflux for the great saphenous vein and for the small saphenous vein, and rates of great saphenous vein and small saphenous vein reflux were analyzed for both sexes. Results: The overall prevalence of saphenous vein reflux was 45%. Males had significantly higher great saphenous vein reflux prevalence than females ( p < 0.001). The most common great saphenous vein reflux pattern in females was segmental reflux and the most common pattern in males was proximal reflux. Conclusions: Saphenous vein reflux is common in C2 patients and is more frequent in males. Standardization of classifications of reflux patterns is very important for correct management of the disease.